Impact of foreign direct investment on income distribution in Malaysia: Social accounting matrix framework - Harun, Mukaramah; Che Mat, Siti Hadijah; Abdul Jalil, Ahmad Zafarullah (2012)
This paper presents the construction of Malaysia’s SAM to analyze foreign direct investment impact on income distribution in Malaysia.The paper will describe the structure of SAM with its detail aggregation and disaggregation of accounts related to the above issue.In this SAM the detail framework of the component of foreign direct investment in various sectors, production sectors and household groups are essential to analyze different effects from different components of foreign direct investment on the household’s income distribution among different household groups.This structure of SAM would answer the question of either and which component of foreign direct investment will benefit the most to the poor.Other accounts such as accounts for companies, accounts for government, and account for the Rest of the World are at the aggregate form.